Biology and ecology of anchialine environments: a review. / Biología y ecología de ambientes anquihalinos: una revisión. - Romero, Oriana R. (Anartia, 2020)
Resumen The term anchialine (from the Greek anchihalos, or “near the sea”) was initially proposed to describe open saltwater or brackish pools, both of volcanic and karstic origin, without surface connection to the sea, which fluctuates with the tides (Holthuis 1973). However, with the discovery of similar pools within caves, a more rigorous definition of the term was suggested, referring to haline water bodies with limited exposure to air and with underground networks that connect with seawater, presenting influence both of the marine and terrestrial environment, but with attenuated effect (Stock et al. 1986). Recently, Bishop et al. (2015) unified the knowledge of this ecosystem, redefining this term more broadly as, a subterranean estuary or zone of encounter and interaction of the freshwater and seawater in submerged caves or galleries, where the only connection with the surface is through small holes which provide portals into these systems.